Will Environmental Regulations lead to China’s outward Foreign Direct Investment?: A Quasi Natural Experiment Based on China’s Carbon Emission Trading Pilot Policy - Cao, Yanzhihui; Yin, Siyu; Luo, Jiabao; Li, Deyu (International Journal of Global Economics and Management, 2024)
Foreign direct investment (OFDI) is an important part of China’s "going global" strategy. With the continuous expansion and rapid development of OFDI in China, domestic environmental problems are becoming increasingly severe. Therefore, China has established a pilot policy of Carbon Emission Trading System (ETS) to address environmental issues. This article takes the implementation of ETS pilot policies as a quasi natural experiment, uses the double difference method (DID model) to empirically test whether ETS pilot policies will lead to OFDI, and uses the composite control method for robustness testing to supplement and expand the conclusions of the DID model. In addition, incorporate the "Pollution Shelter Hypothesis" and "Porter Hypothesis" into the same framework to explore the impact mechanism of ETS pilot policies on OFDI. Based on the conclusions drawn, it is recommended to further improve the design of carbon trading systems in pilot areas and establish a national carbon emission trading system to enhance the quality of China’s outward foreign direct investment.